Assesment of Physical Value Kampung Batik Jetis Towards Sustainable Heritage Development - Fairuz Mutia; Endang Titi Sunarti BD; Ima Defiana (IPTEK Journal of Proceedings Series, 2018)
Sidoarjo, like other cities in Indonesia also has the old town area. It is taken up by the Government of Sidoarjo with a tourism development plan regarding this potential object. Kampung Batik Jetis while being part of the old town area has the potential value for long occupancy also has the good value for becoming a cultural tourism, namely batik. However, the condition of Kampung Batik Jetis currently eligible to become a tourist destination. In fact, Kampung Batik Jetis is a tourist village that has the potential to be enjoyed on foot toward the batik’s gallery, the batik’s workshop, the food court area while enjoying the beauty of the old buildings there. This study aims to explore the physical aspects of Kampung Batik Jetis, related to the movement by the residents and tourists